2022
DOI: 10.1111/ejh.13783
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term safety and efficacy of ravulizumab in patients with paroxysmal nocturnal hemoglobinuria: 2‐year results from two pivotal phase 3 studies

Abstract: Objectives: The complement component 5 (C5) inhibitor ravulizumab demonstrated non-inferiority to eculizumab following 26 weeks of treatment in complement inhibitor-naïve and complement inhibitor-experienced patients with paroxysmal nocturnal hemoglobinuria (PNH; studies 301 and 302, respectively). This study aims to describe the results of both studies from 27 weeks to 2 years.Methods: Patients (N = 441) continued to receive ravulizumab throughout the extension period. Efficacy endpoints included lactate dehy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…As the key component of the alternative pathway, the C3 convertase (C3bBb), is predominantly activated locally on cell surfaces, alternative pathway-driven diseases often manifest locally. However, several of these diseases also display signs of systemic pathway activation, for example, through the production of soluble complement activation and inactivation Genetic: Mutations in the X-linked phosphatidylinositol glycan class A (PIG-A) gene on some hematopoietic stem cell clones reduces membrane expression the C3bBb regulator CD55 and the C9 regulator CD59 135 Functional: Erythrocytes from conditional PIG-A −/− mice show sensitivity to complement attack, 136,137 PNH patient erythrocytes are susceptible to complement lysis 138 Pharmacological: Clinical efficacy of eculizumab 139 and ravulizumab 140 116 and humanized C3 mice lacking C3 regulation by (murine factors 152 ) show C3G-like disease Pharmacological: Case report for efficacy of eculizumab in C3G 153,154 Danicopan BCX9930 Iptacopan 2. Autoantibody-mediated diseases with secondary involvement of the AP…”
Section: Protot Ypi C Al D Is E a S E S With Hyper Ac Tive Alternativ...mentioning
confidence: 99%
“…As the key component of the alternative pathway, the C3 convertase (C3bBb), is predominantly activated locally on cell surfaces, alternative pathway-driven diseases often manifest locally. However, several of these diseases also display signs of systemic pathway activation, for example, through the production of soluble complement activation and inactivation Genetic: Mutations in the X-linked phosphatidylinositol glycan class A (PIG-A) gene on some hematopoietic stem cell clones reduces membrane expression the C3bBb regulator CD55 and the C9 regulator CD59 135 Functional: Erythrocytes from conditional PIG-A −/− mice show sensitivity to complement attack, 136,137 PNH patient erythrocytes are susceptible to complement lysis 138 Pharmacological: Clinical efficacy of eculizumab 139 and ravulizumab 140 116 and humanized C3 mice lacking C3 regulation by (murine factors 152 ) show C3G-like disease Pharmacological: Case report for efficacy of eculizumab in C3G 153,154 Danicopan BCX9930 Iptacopan 2. Autoantibody-mediated diseases with secondary involvement of the AP…”
Section: Protot Ypi C Al D Is E a S E S With Hyper Ac Tive Alternativ...mentioning
confidence: 99%
“… 28 , 57 , 58 However, there was one fatal case of meningococcal sepsis 2.2 years after a patient received their first dose of ravulizumab. 88 …”
Section: Management Of Pnh and The Impact Of C5 Inhibitorsmentioning
confidence: 99%
“…According to the results from pivotal phase 3 clinical trials of eculizumab and ravulizumab in PNH, 17 , 28 , 29 , 43 , 57 , 58 , 88 and the findings of a 10-year eculizumab pharmacovigilance analysis (in patients with PNH and atypical hemolytic uremic syndrome), 44 both drugs are well tolerated. The most frequently reported adverse events were headache, nasopharyngitis, fatigue, and upper respiratory tract infection, and no new safety risks apart from meningococcal infection were reported.…”
Section: Management Of Pnh and The Impact Of C5 Inhibitorsmentioning
confidence: 99%
“…Phase 3 clinical trials demonstrated comparable safety and tolerability of eculizumab and ravulizumab. 37,38 Long-term experience of using eculizumab provided evidence that mitigates initial concerns about infectious events. To minimize the risk of meningococcal infections, associated with complement inhibitors, vaccination and monitoring are recommended.…”
Section: Thrombotic Burden Of Hemolytic Diseases In Pregnancy Paroxys...mentioning
confidence: 99%